2003
DOI: 10.1021/jo020516w
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanates of Nα-[(9-Fluorenylmethyl)oxy]carbonyl Amino Acids: Synthesis, Isolation, Characterization, and Application to the Efficient Synthesis of Urea Peptidomimetics

Abstract: The Curtius rearrangement of Fmoc-amino acid azides 1 was carried out in toluene by refluxing the solution for 30 min. The resulting isocyanates 2 have been isolated as crystalline solids and are fully characterized by IR, (1)H NMR, (13)C NMR, and mass spectra. They are found to be stable for several months when stored at 4 degrees C. The acyl azides of Asp, Glu, Ser, Tyr, and Lys with side-chain protection having tert-butyl, benzyl, and Boc groups were also converted to the corresponding isocyanates 2h-m. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 39 publications
(31 reference statements)
0
30
0
Order By: Relevance
“…The synthetic utilities of N -protected amino isocyanates in the preparation of peptidomimetics like peptidylureas have been described in the literature [44]. Herein, we present a useful application of amino acid derived isocyanates in the synthesis of the N-formylated gem-diamines by the reaction of N-protected amino isocyanates with formic acid in the presence of nano MgO (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…The synthetic utilities of N -protected amino isocyanates in the preparation of peptidomimetics like peptidylureas have been described in the literature [44]. Herein, we present a useful application of amino acid derived isocyanates in the synthesis of the N-formylated gem-diamines by the reaction of N-protected amino isocyanates with formic acid in the presence of nano MgO (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…They were converted to corresponding acid azides via mixed anhydride. The Fmoc-peptidyl azides were subjected to Curtius rearrangement to furnish corresponding isocyanates (Patil et al, 2003;Sureshbabu et al, 2006) by exposing the solution of acid azide in toluene to microwave irradiation for 45 s (Scheme 2). All the peptidyl isocyanates were isolated as stable crystalline solids that can be stored under low temperature for long time.…”
Section: Resultsmentioning
confidence: 99%
“…17 Current strategies to synthesize N a -protected urealinked peptides are predominantly based on Curtius and Hoffmann rearrangements. Sureshbabu et al, reported an elegant procedure for the synthesis of Fmoc protected a-ureido peptides, 18 oligoureas, 19 and a variety of substituted phenyl-(9-fluorenylmethoxycarbonylamino)methyl carbamates 20 through the classical Curtius rearrangement employing a series of isocyanates derived from stable N aFmoc amino acid azides. 21 Guichard and co-workers, reported the stepwise synthesis of N,N 0 -urea-linked oligomers using O-succinimidyl (N a -urethane protected) methyl carbamates.…”
Section: Introductionmentioning
confidence: 99%